Des saints et des martyrs hommage à Alain Dierkens - D'Hainaut-Zveny, Brigitte (Problèmes d'histoire des religions, 2018)
This volume of Problems in the History of Religions is dedicated to Professor Alain Dierkens, a medievalist specializing in the study of religion and director of the collection from 1991 to 2012.